Absence of morphological and molecular correlates of sarcopenia in the macaque tongue muscle styloglossus - Sokoloff, Alan J. (Exp Gerontol, 2016)
INTRODUCTION: Equivocal decline of tongue muscle performance with age is compatible with resistance of the tongue to sarcopenia, the loss of muscle volume and function that typically occurs with aging. To test this possibility we characterized anatomical and molecular indices of sarcopenia in the macaque tongue muscle styloglossus (SG). METHODS: We quantified myosin heavy chain (MHC), muscle fiber MHC phenotype and size and total and phosphorylated growth- and atrophy-related proteins by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), immunoblot and immunohistochemistry (IHC) in the SG in twenty-four macaque monkeys (Macaca rhesus, age range 9 months to 31 years) categorized into Young (<8 years of age), Middle-aged (15–21 years of age) and Old (> 22 years of age) groups. RESULTS: In Young, Middle and Old age groups, by SDS-PAGE MHCI comprised ~1/3 and MHCII ~2/3 of total MHC. MHCI relative frequency was lower and MHCII higher in Middle versus Young (p=0.0099) and Middle versus Old (p=0.052). Relative frequencies of MHC fiber phenotype were not different by age but were different by phenotype (rates 233, 641 and 111 per 1000 fibers for MHCI, MHCII and MHCI-II respectively, P = 0.03). Few or no fibers were positive for developmental MHC. Mean cross-sectional area (CSA) was not different among the three age groups for MHCII and MHCI-II; however MHCI fibers tended to be larger in Middle versus Old and Young (mean = 2257 um(2), 1917 um(2) (p=0.05) and 1704 um(2) (p=0.06), respectively). For each age group, mean CSA increased across MHC phenotype (lowest mean CSA for MHCI and highest mean CSA for MHCII). Spearman analysis demonstrated age-related increases in total p70 ribosomal protein S6 kinase (P70), phosphorylated P70(421/424), phosphorylated P38 mitogen-activated protein kinase and muscle atrophy F-Box, a trend to age-related decrease in total extracellular signal-regulated kinase (ERK), and no age-related change in total protein kinase B (Akt/PKB), phosphorylated Akt, phosphorylated ERK, phosphorylated c-Jun N-terminal kinase (JNK46) and phosphorylated P70(389). CONCLUSION: Common anatomical and molecular indices of sarcopenia are absent in our sample of macaque SG. Relative frequencies of MHCII protein and phenotype are preserved with age. Although MAFbx expression increases with age, this is not associated with fiber atrophy, perhaps reflecting compensatory growth signaling by p70. The resistant nature of the styloglossus muscle to sarcopenia may be related to routine activation of tongue muscles in respiration and swallowing and the preservation of hypoglossal motoneuron number with age.